A head coil system with an integrated orbiting transmission point source mechanism for attenuation correction in PET/MRI. (12th November 2018) - Renner, A; Rausch, I; Cal Gonzalez, J; Frass-Kriegl, R; Navarro de Lara, L I; Sieg, J; Laistler, E; Glanzer, M; Dungl, D; Moser, E; Beyer, T; Figl, M; et al.
Abstract: The combination of positron emission tomography (PET) and magnetic resonance imaging (MRI) provides a benefit for diagnostic imaging. Still, attenuation correction (AC) is a challenge in PET/MRI compared to stand-alone PET and PET-computed tomography (PET/CT). In the absence of photonic transmission sources, AC in PET/MRI is usually based on retrospective segmentation of MR images or complex additional MR-sequences. However, most methods available today are still challenged by either the incorporation of cortical bone or substantial anatomical variations of subjects. This leads to a bias in quantification of tracer concentration in PET. Therefore, we have developed a fully integrated transmission source system for PET/MRI of the head to enable direct measurement of attenuation coefficients using external positron emitters, which is the reference standard in AC. Based on a setup called the 'liquid drive' presented by Jones et al (1995) two decades ago, we built a head coil system consisting of an MR-compatible hydraulic system driving a point source on a helical path around a 24-channel MR-receiver coil to perform a transmission scan. Sinogram windowing of the moving source allows for post-injection measurements. The prototype was tested in the Siemens Biograph mMR using a homogeneous water phantom and a phantom with air cavities and a Teflon (PTFE) cylinder. The second phantom was measured both with and without emission activity. For both measurements air, water and Teflon were clearly distinguishable and homogeneous regions of the phantom were successfully reproduced in the AC map. For water the linear attenuation coefficient was measured as (0.096 ± 0.005) cm −1 in accordance with the true physical value. This combined MR head coil and transmission source system is, to our knowledge, the first working example to use an orbiting point source in PET/MRI and may be helpful in providing fully-quantitative PET data in neuro-PET/MRI.